Dupuytrens Contracture of the Hand and Its Treatment by Open Palm Technique - F. M. Tripathi; J. K. Sinha; V. Bhattacharya; A. K. Chaudhury; O. P. Singh (Indian Journal of Plastic Surgery)
Two cases of Dupuytrens contracture of the hand treated by open palm technique have been reported for their clinical interest.